Geometrical dimensioning and tolerancing for design, manufacturing and inspection a handbook for geometrical product specifications using ISO and ASME standards - Henzold, G. (Butterworth-Heinemann, 2006)
The complete geometrical tolerancing reference, from principles through to inspection, for all engineers designing components to the latest standards.
Previous ed. published as: Handbook of geometrical tolerancing. Chichester : Wiley, 1995.
Keywords: Tolerance (Engineering); Engineering drawings.; elektronické knihy; electronic books